Makishimaizu Majikku: Borrowing Patterns of Spell Names in Engrish in Overlord Anime - Al Fayd, Ahmad Najib; Fahrurizky, Favian Jiwani; Muhammad, Kahfi (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This study explores how English words are borrowed and changed into magical spell names (Engrish) in the anime Overlord. The research uses Honna’s (1995) theory of borrowing patterns to identify how English is adapted into Japanese and given new meanings in the anime’s magic system. The study applies a descriptive qualitative method, using data from both the dialogue and the visual appearance of spells in Overlord. The analysis follows Spradley’s (1980) four steps: domain, taxonomy, componential, and cultural theme analysis. The findings show that only two of Honna’s seven borrowing patterns appear in the anime: Semantic Narrowing and Shift and Japanese Phrasings of English. In the first, English words such as Electrosphere, Shield Wall, and Indomitability lose part of their original meaning and gain a new, more specific sense as magic spells. In the second, phrases like Grasp Heart, Anti-life Cocoon, and Greater Teleportation show how Japanese combines English words to create new and unique spell names. These adaptations make the magic system sound more powerful and consistent. Overall, the study concludes that Overlord uses English borrowings not only for meaning but also for artistic style, helping to build a creative and recognizable fantasy world. The findings highlight how linguistic borrowing functions as a stylistic and cultural tool in Japanese media, showing that English serves not only as a source of vocabulary but also as a means of expressing identity, creativity, and globalization in anime. Future studies could compare Overlord with other anime to examine similar borrowing patterns and explore how audiences interpret Engrish spell names in relation to authenticity and world-building.